Alzheimer Dan Gejala Sistem Saraf (Neurologis) Akibat Pestisida: Alzheimer's and the Symptoms of the Nervous System (Neurological) Due to Pesticides - Sulistyani Prabu Aji; Sapja Anantanyu (YCMM, 2022)
Alzheimer's disease is a progressive neurodegenerative disease characterized by decreased cognitive function, memory loss or memory loss, and dementia syndrome. Alzheimer's disease will continue to increase and is expected to reach 1,894,000 cases in 2030 and continue to 3,980,000 cases in 2050. The type of research conducted is in the form of narrative review research. Research data is secondary data taken from national and international research articles. The results obtained are then grouped and synthesized in a narrative way.